Economics : Ready Notes - Colander, David C. (Irwin, 1993)
Poroduction possibility curve table and graph. Efficiency and ineffciency. Slopes of curves. From individual demands to a market demands curve. Transformation of factors of production into consumable goods. The marriage of supply and demand...